Practicing stewardship: EU biofuels policy and certification in the UK and Guatemala - Helliwell, Richard; Tomei, Julia (Springer, 2017)
Biofuels have transitioned from a technology expected to deliver numerous benefits to a highly contested socio-technical solution. Initial hopes about their potential to mitigate climate change and to deliver energy security benefits and rural development, particularly in the Global South, have unravelled in the face of numerous controversies. In recognition of the negative externalities associated with biofuels, the European Union developed sustainability criteria which are enforced by certification schemes. This paper draws on the literature on stewardship to analyse the outcomes of these schemes in two countries: the UK and Guatemala. It explores two key issues: first, how has European Union biofuels policy shaped biofuel industries in the UK and Guatemala? And second, what are the implications for sustainable land stewardship? By drawing attention to the outcomes of European demand for biofuels, we raise questions about the ability of European policy to drive sustainable land practices in these two cases. The paper concludes that, rather than promoting stewardship, the current governance framework effectively rubberstamps existing agricultural systems and serves to further embed existing inequalities.